Advances in Computer Systems Architecture 12th Asia-Pacific Conference, ACSAC 2007, Seoul, Korea, August 23-25, 2007, Proceedings - Choi, Lynn; Paek, Yunheung; Cho, Sangyeun (Theoretical Computer Science and General Issues, 2007)
On behalf of the program and organizing committee members of this conference, we th are pleased to present you with the proceedings of the 12 Asia-Pacific Computer Systems Architecture Conference (ACSAC 2007), which was hosted in Seoul, Korea on August 23-25, 2007. This conference has traditionally been a forum for leading researchers in the Asian, American and Oceanian regions to share recent progress and the latest results in both architectural and system issues. In the past few years the c- ference has become more international in the sense that the geographic origin of p- ticipants has become broader to include researchers from all around the world, incl- ing Europe and the Middle East. This year, we received 92 paper submissions. Each submission was reviewed by at least three primary reviewers along with up to three secondary reviewers. The total number of completed reviews reached 333, giving each submission 3.6 reviews on average. All the reviews were carefully examined during the paper selection process, and finally 26 papers were accepted, resulting in an acceptance rate of about 28%. The selected papers encompass a wide range of topics, with much emphasis on hardware and software techniques for state-of-the-art multicore and multithreaded architectures.